A Scintigraphic Investigation of Magnetic Field Therapy on the Equine Third Metacarpus - Kobluk, C. N.; Johnston, G. R.; Lauper, Linda (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Scintigraphy was performed in the vascular, soft tissue and bone phase to demonstrate increased blood flow resulting from the local application of a permanent magnetic pad on the equine third metacarpus using a crossover trial in eight horses.The results of the vascular phase showed a highly significant (p <0.01) increase in counts associated with magnet application. An increase in counts results from increased blood flow carrying more radionuclide to the area investigated. Fifteen of the sixteen limbs tested showed an increased vascular response. The soft tissue phase had a highly significant response (p = 0.01) with thirteen of the sixteen limbs showing increased activity. The bone phase also had a highly significant response (p <0.01) with fourteen of the sixteen limbs showing increased activity.This study shows that the Equinepad® applied to the third metacarpus of the horse increases the circulation and metabolic activity of the soft tissue and bone. These effects show some variability in degree and occur in the majority of limbs tested.Scintigraphy was performed in the vascular, soft tissue and bone phase using a cross over trial to demonstrate increased blood flow and metabolic activity as a result of the local application of a permanent magnetic pad on the equine metacarpus. A highly significant increase was evident in the three phases.
Keywords: Equine; scintigraphy; magnetic field therapy